- The Impact Level of Administrative leadership on Organizational Development in universities - A Field Study on Female Employees of King Abdul Aziz University in Jeddah - Al - Hamdan, Safaa bint Abdullah (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed to determine the impact level of Administrative Leadership on the Organizational Development in King Abdulaziz University -Head Quarter- based on the perspective of its Female administrative staff those who are this study population consist of، which has (1633) member، the researcher had used the Simple Random Sampling method with a size of (311) member، the questionnaires have been distributed electronically and printed، 290 questionnaires was retrieved، all of them was valid for the statical analysis with a percentage of (%93) to the required sample size، the researcher also had used Descriptive Analytical Approach to conclude this study results، some of the statical techniques from (SPSS) program were adopted such as: Arithmetic Mean، Standard Deviation، Correlation Coefficient and Regression Models. The study has found several results، the most important of which are: there is statically significant effect of the Administrative Leadership on the Organizational Development، there is a positive relationship between Administrative Leadership styles both the Democratic and Laissez-Fair with the Organizational Development، there is an inverse relationship between the Autocratic Leadership and Organizational Development، there is statically significant differences at (0.05≥????) in the administrative employees opinion about the Autocratic style on account of age differentiation، there is statically significant differences at (0.05≥????) in the administrative employees opinion about the technology dimension due to the variation of their experience. The study recommended the need of strengthen the application of Democratic Leadership and to provide the chance to employees to share their opinions and suggestions because of it’s positive Impact on the success of the progress of Organizational Development، and to conduct more scientific studies and field research that aims to recognize the leadership and its role in Organizational Development.